Efficacy of milbemycin oxime/afoxolaner chewable tablets (NEXGARD SPECTRA(®)) against Capillaria aerophila and Capillaria boehmi in naturally infected dogs - Di Cesare, Angela (Parasit Vectors, 2021)
BACKGROUND: Capillaria aerophila and Capillaria boehmi parasitize the respiratory system of wild and domestic carnivores. Capillaria aerophila inhabits the trachea and bronchi of dogs and cats, while C. boehmi affects the nasal cavities and sinuses of dogs. In dogs the infection may be subclinical or characterized by varying respiratory distress. METHODS: The present study evaluated the efficacy of an oral formulation containing milbemycin oxime and afoxolaner (NEXGARD SPECTRA(®)) in dogs naturally infected with C. aerophila and/or C. boehmi from three enzootic areas of Italy. Dogs were enrolled pending fecal examination and molecular confirmation of respiratory capillarioses. Dogs were allocated in two groups: Group 1 (G1, 25 dogs), treated with a negative control product with no anthelmintic activity (afoxolaner, NEXGARD(®)), and Group 2 (G2, 26 dogs), treated with NEXGARD SPECTRA(®). At the day of treatment administration (Day 0), all dogs were clinically examined. Dogs were again subjected to clinical and fecal examinations at Days 28 (± 4) and 56 (± 2). The primary criterion for treatment efficacy was the reduction of fecal Capillaria egg counts in G2 compared with G1. The regression of/recovery from baseline clinical signs was considered as a further efficacy criterion. RESULTS: Percentage reduction of fecal Capillaria egg counts in the NEXGARD SPECTRA(®) group compared to the control group was > 97% on Day 28 and 100% on Day 56, respectively (p < 0.05 for both time points). Twelve of the 13 dogs in the NEXGARD SPECTRA(®) group with respiratory signs prior to treatment were free of clinical signs at the end of the study. Conversely, the six control group dogs with respiratory signs prior to treatment remained symptomatic. CONCLUSIONS: Results of the present study showed that NEXGARD SPECTRA® was safe and highly efficacious in the reduction of C. aerophila and C. boehmi eggs after one treatment with a complete reduction of the egg output after the second administration associated with a recovery from respiratory signs. [Image: see text]